Comparative effectiveness of botulinum toxin versus non-surgical treatments for treating lateral epicondylitis: a systematic review and meta-analysis. (February 2018) - Lin, Yu-Ching; Wu, Wei-Ting; Hsu, Yu-Chun; Han, Der-Sheng; Chang, Ke-Vin
Objectives: To explore the effectiveness of botulinum toxin compared with non-surgical treatments in patients with lateral epicondylitis. Methods: Data sources including PubMed, Scopus, Embase and Airity Library from the earliest record to February 2017 were searched. Study design, patients' characteristics, dosage/brand of botulinum toxin, injection techniques, and measurements of pain and hand grip strength were retrieved. The standardized mean differences (SMDs) in pain relief and grip strength reduction were calculated at the following time points: 2-4, 8-12, and 16 weeks or more after injection. Results: Six randomized controlled trials (321 participants) comparing botulinum toxin with placebo or corticosteroid injections were included. Compared with placebo, botulinum toxin injection significantly reduced pain at all three time points (SMD, -0.729, 95% confidence interval [CI], -1.286 to -0.171; SMD, -0.446, 95% CI, -0.740 to -0.152; SMD, -0.543, 95% CI, -0.978 to -0.107, respectively). Botulinum toxin was less effective than corticosteroid at 2-4 weeks (SMD, 1.153; 95% CI, 0.568-1.737) and both treatments appeared similar in efficacy after 8 weeks. Different injection sites and dosage/brand did not affect effectiveness. Botulinum toxin decreased grip strength 2-4 weeks after injection, and high equivalent dose could extend its paralytic effects to 8-12 weeks. Conclusions: When treating lateral epicondylitis, botulinum toxin was superior to placebo and could last for 16 weeks. Corticosteroid and botulinum toxin injections were largely equivalent, except the corticosteroid injections were better at pain relief in the early stages and were associated with less weakness in grip in the first 12 weeks.